Republic of Fiji : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that growth in Fiji in 2013 accelerated to 4.6 percent. Consumption and investment indicators suggest continued strength in 2014, with economic growth projected at 3.8 percent. Headline inflation is currently low as imported commodity and food prices have remained stable. The Reserve Bank of Fiji lowered its policy rate to 0.5 percent in 2011, and monetary policy has been on hold since then. In response to lower rates and improved confidence, net domestic credit accelerated in the first half of 2014. Based on developments in the first half of 2014, the deficit financing target is on track to be met.